Nature of the interactions between hypocrealean fungi and the mutualistic fungus of leaf-cutter ants - Varanda-Haifig, Sadala Schmidt [UNESP] (2017)
Leaf-cutter ants cultivate and feed on the mutualistic fungus, Leucoagaricus gongylophorus, which is threatened by parasitic fungi of the genus Escovopsis. The mechanism of Escovopsis parasitism is poorly understood. Here, we assessed the nature of the antagonism of different Escovopsis species against its host. We also evaluated the potential antagonism of Escovopsioides, a recently described fungal genus from the attine ant environment whose role in the colonies of these insects is unknown. We performed dual-culture assays to assess the interactions between L. gongylophorus and both fungi. We also evaluated the antifungal activity of compounds secreted by the latter on L. gongylophorus growth using crude extracts of Escovopsis spp. and Escovopsioides nivea obtained either in (1) absence or (2) presence of the mutualistic fungus. The physical interaction between these fungi and the mutualistic fungus was examined under scanning electron microscopy (SEM). Escovopsis spp. and E. nivea negatively affected the growth of L. gongylophorus, which was also significantly inhibited by both types of crude extract. These results indicate that Escovopsis spp. and E. nivea produce antifungal metabolites against the mutualistic fungus. SEM showed that Escovopsis spp. and E. nivea maintained physical contact with the mutualistic fungus, though no specialised structures related to mycoparasitism were observed. These results showed that Escovopsis is a destructive mycoparasite that needs physical contact for the death of the mutualistic fungus to occur. Also, our findings suggest that E. nivea is an antagonist of the ant fungal cultivar.